Identifying the resonance curve of a system subjected to linear and quadratic parametric excitations (case with damping) - Dinh, Nguyen Van; Chi, Tran Kim (Vietnam Journal of Mechanics, 1999)
In [3], a quasi linear oscillating system simultaneously subjected to linear and cubic parametric excitations has been studied. In the present paper, we examine the case in which the linear and quadratic parametric excitations are present. The asymptotic method [ 1] is applied. We are interested in the method of identifying the resonance curve. The results obtained show that the "associated" equations can be used.